PEMBELAJARAN MAHĀRAT AL-KALĀM DI SMP ALAM BANYUWANGI ISLAMIC SCHOOL - Amirul Mukminin; Aisyatul Hanun; Ahmad Zaini (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
Maharat al-kalam is one of the most important language skills, because with this maharat someone communicates with one another, and also as a transmitter of information that someone wants to convey. However, not all institutions can implement daily learning activities using Arabic as has been implemented in SMP Alam Banyuwangi Islamic School. So that it is considered a role model for other institutions that want to implement maharat al-kalam due to its achievements so far in optimizing speaking Arabic in the learning process, even in everyday life. The research method used in this research is qualitative with case studies and data collection techniques through observation, documentation, and in-depth interviews. The research objectives in this article are: First, to analyze the implementation of mahārat al-kalām learning approaches, methods and techniques in SMP Alam Banyuwangi Islamic School Banyuwangi. Second, explain the problems of implementing the approach, method and technique of learning mahārat al-kalām at the institution. Third, solutions in the implementation of mahārat al-kalām learning approaches, methods and techniques at SMP Alam Banyuwangi Islamic School Banyuwangi.